INTELLIGENT DIGITAL SOLUTIONS FOR INCREASING OPERATIONAL EFFICIENCY AND LABOR PRODUCTIVITY IN ELECTRIC POWER INDUSTRY - V. Ya. Afanasev; N. V. Vorontsov (Вестник университета)
We can already say with certainty, that the basis for the development of modern electric power industry will soon be intellectual, digital transformation of production assets, which in itself opens a new approach to the problem of increasing operational efficiency and labor productivity. The main difficulty in this way is, that the existing research of digital technologies do not take into account the applied aspects of the implementation of its products according to the industry specifics and business goals of companies – market entities. In this paper, the analysis and classification of commercial IT products have been made by subject groups of solutions, that meet the needs of specific target areas of activity of electric power companies. The conceptual description of the subject groups of digital solutions on the basis of known examples and practices of their application has been adduced.